(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The relationship between financial results and market value is crucial for entrepreneurial entities striving to achieve long-term sustainability and growth. This paper explores the impact of financial performance indicators such as profitability, revenue growth, and capital structure on the market value of entrepreneurial entities. By analyzing the interaction between these variables, the study aims to understand how effective financial management can enhance a business’s overall valuation in a competitive market.